Interplay Between Human Gut Bacteria Escherichia coli and Lactobacillus mucosae in the Occurrence of Neuropsychiatric Disorders in Mice - Kim, Jeon-Kyung; Lee, Kyung-Eon; Lee, Sang-Ah; Jang, Hyo-Min; Kim, Dong-Hyun (Frontiers in Immunology, 2020)
To understand the roles of human gut bacteria in the occurrence of neuropsychiatric disorders, we isolated inflammatory Escherichia coli K1 and anti-inflammatory Lactobacillus mucosae from healthy human feces and examined their effects on the occurrence of altered microbiota, cognitive decline, and depression in mice. Oral gavage of Escherichia coli K1 caused colitis, cognitive decline, and depression in mice in the elevated plus maze, tail suspension, and forced swimming tasks. However, NK41 treatment reduced K1-induced cognitive decline and anxiety/depression. Furthermore, NK41 treatment increased K1-suppressed brain-derived neurotrophic factor (BDNF) expression and BDNF+/NeuN+ cell population and suppressed K1-induced NF-κB activation and LPS+/Iba1+ and NF-κB+/Iba1+ (microglial) cell populations in the hippocampus. NK41 treatment also suppressed K1-induced TNF-α and LPS levels in the blood and TNF-α expression, myeloperoxidase activity, NF-κB+/CD11c+ and CD11b+/CD11c+ cell populations in the colon. Furthermore, NK41 treatment decreased K1-induced colonic MUC2 expression, gut Proteobacteria population, and fecal LPS levels and modified the bacterial abundance related to polysaccharide breaking and biosynthesis. In conclusion, the overgrowth of inflammatory bacteria such as Escherichia coli in the gastrointestinal tract can cause neuropsychiatric disorders with gut microbiota alteration and the superiority of anti-inflammatory bacteria such as Lactobacillus mucosae can alleviate neuropsychiatric disorders with the attenuation of altered microbiota.